Terapia dziecka ze spektrum autyzmu = Therapy of a child with autism spectrum disorder - Markowska, Magdalena (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
This article is based on my speech therapy dissertation written in 2004 as a part of my final examination at Wroclawski University. It is about 8 year old girl who suffers from some autistic features that coexist with mental retardation. This girl has some autistic features such as isolating, stereotypies, echolalia and not communicating with other people. These difficulties are strongly connected with language- lack of understanding the language actually.
Keywords: autyzm; upośledzenie umysłowe; echolalia; stereotypie; autism; mental retardation; stereotypies